1997
DOI: 10.1111/j.1460-2695.1997.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

On Determining Stress Intensity Factors for Mixed Mode Cracks From Thermoelastic Data

Abstract: An alternative methodology is presented for determining stress intensity factors for cracks subject to mixed-mode displacements. The methodology involves thermoelastic data generated from a SPATE (Stress Pattern Analysis by Thermal Emission) system and has been adapted from one used successfully in photoelasticity. The thermoelastic data is collected throughout the elastic stress field dominated by the crack tip singularity. The stress field is described using a Fourier series within Muskhelishvili's approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 14 publications
4
56
0
Order By: Relevance
“…Two different Fig. 1 Stress state ahead of a crack tip mathematical descriptions have been used to determine the SIFs from TSA data: Williams's equations and the Muskhelishvili solutions [15]. However, since the Muskhelishvili approach makes it only possible to determine the SIFs, the only applicable model to determine the T-stress and SIF is Williams's formulation.…”
Section: Elastic Parameters Determination Using Tsamentioning
confidence: 99%
See 1 more Smart Citation
“…Two different Fig. 1 Stress state ahead of a crack tip mathematical descriptions have been used to determine the SIFs from TSA data: Williams's equations and the Muskhelishvili solutions [15]. However, since the Muskhelishvili approach makes it only possible to determine the SIFs, the only applicable model to determine the T-stress and SIF is Williams's formulation.…”
Section: Elastic Parameters Determination Using Tsamentioning
confidence: 99%
“…In recent years, thermoelastic stress analysis (TSA) has proved to be an ideal technique for the determination of mode I, mode II, and mixed SIFs [11][12][13][14][15]. Therefore the aim of this work was to develop these methodologies to determine the Tstress in addition to the SIF.…”
Section: Introductionmentioning
confidence: 99%
“…The approach which was used in the current experiments was developed by Tomlinson et al 4 . A Newton-Raphson iteration combined with a least squares approach is used to fit the equations describing the stress field around the crack tip, based on Mushkelishvili's approach, to the experimental data.…”
Section: Determination Of K I and K Ii From Thermoelastic Datamentioning
confidence: 99%
“…No reasons could be given for the unusually large differences and plans for further investigation were indicated. The majority of the published data have been for cracks under predominantly mode I loading and the only data for predominantly mode II loading showed a difference between theory and experiment of up to 40% 4 . It was suggested that the theoretical solution may not be reliable at this extreme notch geometry for which there was only one numerical and no other experimental study in support.…”
Section: Introductionmentioning
confidence: 99%
“…Although accurate analyses have been performed for opening mode cracks and slots, only limited progress has been made for the determination of stress intensity factors for mixed-mode cracks using thermoelastic techniques 4,5,6,7,8 . Recently published data on the subject 5 show good agreement between theory and experiment for both K I and K II for central slots and cracks, and edge slots.…”
Section: Introductionmentioning
confidence: 99%